An Unpublished Drawing for pulpit in the Cathedral of Cosenza by Andrea Maggiore, Niccolò Ciolli and Antonio Grasso - Rinaldo D'Alessandro (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2023)
This contribution analyzes a completely unknown 16th century drawing. In the document, the author identifies a lost project for a pulpit in the Cathedral of Cosenza, draw up by Andrea Maggiore, Niccolò Ciolli and Antonio Grasso. The reconstruction of the drawing’s origin is possible thanks to some valuable indications on the document itself. The discovery allows us to re-analyze the personality of Andrea Maggiore, and his first known work, in the context of the Calabrian renaissance. Andrea Maggiore is especially important for the introduction of coloured marble altars in the region. His works are framed in the general phenomenon of the introduction of a new architectural language in southern Italy with an important reference to the role of his clients: a powerful and sometimes foreign cultural élite.